(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Under the current socio-economic conditions marked by prolonged uncertainty, crisis phenomena, warfare, inflationary risks, and information overload, consumer behavior in Ukraine is undergoing significant transformation. Traditional consumption models are giving way to new approaches, with an increasing role played by digital technologies, self-service, personalized communication, and the demand for fast, flexible solutions. The relevance of this topic stems from the considerable global and national crises over the past five years, particularly the COVID-19 pandemic (2019) and Russia’s full-scale invasion (since February 2022), which have fundamentally changed purchasing power and consumer habits. These shifts demand greater flexibility and adaptation of marketing strategies and tools by businesses. The purpose of the article. The goal of the study is to improve the model of rational behavior of Ukrainian consumers based on the identified key changes and trends in its transformation during crisis. Methods. The theoretical and methodological foundation of the research is based on works by domestic and international scholars studying consumer behavior under uncertainty and crisis conditions. The information base includes scientific, economic, and reference literature, methodological materials, informational portals, and periodicals from Ukraine. A combination of methods and approaches was used: comparative analysis and content analysis of publications and studies by Gradus Research and Deloitte to identify crisis factors affecting purchasing power and consumer habits in the last five years; system analysis and logical generalization to identify key changes in consumer behavior and main trends of its transformation; abstraction and data grouping to determine consumer priorities during uncertainty and crisis; synthesis methods, empirical data generalization, and comparative analysis to formulate major changes in Ukrainian consumer behavior under crisis conditions; modeling and graphoanalytical method to construct the rationality curve of consumer behavior during the crisis period. Results. The study investigates the processes of transformation in the behavior of Ukrainian consumers under conditions of uncertainty and crisis, focusing primarily on changes in their habits and priorities. In particular, a consumer behavior model has been refined, taking into account the influence of external factors (sociocultural, marketing, and especially situational—such as military, economic, and political-legal conditions) and internal factors (psychological, personal, and economic) on the decision-making process. Based on the analysis of the crisis period in Ukraine over the past five years, key trends reflecting the transformation of Ukrainian consumer behavior in situations of crisis and uncertainty have been identified: • Digitalization and technological adoption, evidenced by the growing popularity of online shopping due to time and cost savings, while the share of consumers shopping in traditional stores dropped significantly (from 83% in 2021 to 55% in 2022). • Emotional autonomy and self-care, as consumers increasingly value their own time and gradually return to familiar services (e.g., beauty salons, cafés) during periods of stabilization. • Planned and more rational consumption: 42% of consumers strictly planned their purchases in 2022, compared to 24% in 2021, with priority given to essentials (food, medicine). • High price sensitivity and adaptation to uncertainty: Savings ranging from 47% to 86% depending on the product category, switching to cheaper goods (36%), and reducing the number of items in the shopping basket (40%). • Socially conscious and patriotic consumption: A growing preference for Ukrainian goods and producers (74% in 2024 vs. 69% in 2022), with manufacturer support for the Armed Forces and volunteer initiatives becoming key factors in purchasing decisions. Consumers increasingly trust socially responsible brands. • Decreasing brand and advertising loyalty, with a preference for familiar, trusted brands, and an increase in the search for product/service information and reviews. A consumer rationality curve has been developed, illustrating behavior across different crisis phases: • Crisis onset. Characterized by fear, uncertainty, and a sharp rise in rational behavior, with a focus on prices and planning. At this stage, physiological needs and the need for safety dominate. • Crisis stabilization. A slowdown in the growth of practical behavior, fatigue from uncertainty, a gradual return of familiar products to shopping baskets, and occasional impulsive purchases. • Crisis easing. An increase in the pace of return to pre-crisis market behavior, with more expensive products reappearing. However, by the third year of full-scale war, there is a slight decline in rationality: more consumers pay attention to brands (62% in 2024 vs. 54% in 2022), are willing to try new brands (37%, mainly Ukrainian), and the share of consumers who plan purchases in advance has slightly decreased (from 76% to 73%). Conclusions. Key trends in changing consumer behavior have been identified, including digitalization and technologization; emotional autonomy and self-care; purchase planning and more rational behavior; price sensitivity and adaptation to uncertainty; socially conscious and patriotic consumption, among others. A curve of consumer rationality behavior across different crisis phases has been constructed: crisis onset (sharp increase in rationality), stabilization (fatigue, situational impulsive purchases), and crisis easing (gradual return to usual behavior). A consumer rationality curve during the crisis period was developed, incorporating a composite rationality indicator (purchase planning, cost-saving, conscious choice based on product information analysis) and time. Three main phases of consumer behavior change corresponding to crisis stages—onset, stabilization, and easing—were identified and described. It has been established that post-crisis behavior requires further research, as rationality may remain elevated (due to accumulated experience) or decrease due to the desire to "live in the moment." The identified behavioral characteristics serve as a valuable roadmap for businesses in adapting their marketing strategies.